Impact of financial statements information on market share price of listed insurance firms in Nigeria - Salman, Ramat; Abogun, Segun; Lambo, Isaac Adebukola; Yunus, Abdulrasheed Bolaji; Sanni, Peter Ade (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
In emerging economies, there is an issue of relevant information for investors’ decision. Therefore, this study is carried out to determine the value relevance of financial statements information on Market Share Price of Nigerian listed insurance firms as at 31st December, 2022. Positivism methodology was adopted and as such, ex-post facto design was employed. Consequently, secondary data was used for this research work, obtained from the published annual reports and accounts of the selected insurance firms. The Panel data regression was used to analyze the data. The study found that both dividend per share and solvency margin ratio have positive and significant impact on market price per share (p-value > 5% level of significance). On the other hand, book value per share and earnings per share were found to have insignificant impact on market price per share (p-value > 5% level of significance). The study concludes that dividend per share and solvency margin ratio influenced market price per share of the selected companies in Nigeria and thus recommends that listed insurance companies should do more towards generating adequate profit that will enable payment of dividend to investors and to pay insurers their probable claims whenever the need arises.